2003
DOI: 10.1302/0301-620x.85b1.12468
|View full text |Cite
|
Sign up to set email alerts
|

Aberdeen Colles’ fracture brace as a treatment for Colles’ fracture

Abstract: We carried out a randomised, prospective, multicentre clinical trial of the treatment of Colles' fractures. A total of 339 patients was placed into two groups, those with minimally displaced fractures not requiring manipulation (151 patients) and those with displaced fractures which needed manipulation (188 patients). Treatment was by either a conventional Colles' plaster cast (a control group) or with a prefabricated functional brace (the Aberdeen Colles' fracture brace). Similar results were obtained in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…A Cochrane review on non-operative interventions found no conclusive evidence for the superiority of any immobilisation method in distal radius fractures [ 14 ]. The Aberdeen Colle’s fracture brace is based on three-point fixation and good clinical results has been published [ 15 ]. Although insufficient stability was not mentioned as a motivation for abandoning further development, a patent application combining functional bracing with K-wires suggests that stability might have been a problem [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review on non-operative interventions found no conclusive evidence for the superiority of any immobilisation method in distal radius fractures [ 14 ]. The Aberdeen Colle’s fracture brace is based on three-point fixation and good clinical results has been published [ 15 ]. Although insufficient stability was not mentioned as a motivation for abandoning further development, a patent application combining functional bracing with K-wires suggests that stability might have been a problem [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyapatite-coated wedges of 5, 7.5 or 10 mm sizes are placed in the open wedge and two plates are used for fixation. [39]. …”
Section: Historical Perspectivementioning
confidence: 99%
“…More recently in 1987, Hernigou et al reported their findings from a long-term follow-up of spontaneous osteonecrosis of the knee (SONK) patients who had undergone OWHTO [7]. There are different methodologies and implants that can be used in OWHTO and Koshino et al have described the use of hydroxyapatite wedges in the osteotomy gap [8]. The principal advantages of OWHTO include maintenance of the bone stock, correction of the deformity close to its origin, and no requirement for a fibular osteotomy [6,9].…”
Section: Introductionmentioning
confidence: 99%